Insights into semi-continuous synthesis of iron oxide nanoparticles (IONPs) via thermal decomposition of iron oleate - Egon Götz Höfgen; Sulalit Bandyopadhyay (Discover Nano)
Abstract The increasing demand for magnetic iron oxide nanoparticles (IONPs) in biomedicine necessitates efficient and scalable production methods. Thermal decomposition offers excellent tailoring of the particle properties but its discontinuous batch-operation is restricting scale-up and industrial application. To overcome these challenges, several studies have demonstrated semi-continuous thermal decomposition by slowly injecting the precursor, though only half of them produce magnetite IONPs and even fewer use iron oleate precursors. The available studies are limited, often focusing on single synthesis variables and a comprehensive mapping of the physicochemical properties to reaction conditions is missing. Here we present our investigation of semi-continuous thermal decomposition of iron oleate as a route for the synthesis of magnetic IONPs. We achieved the semi-continuous synthesis of spherical IONPs with properties matching those obtained via the conventional heat-up method. We explored the the effect of multiple synthesis variables, namely addition rate, dwell time, iron oleate amount, oleic acid amount, temperature and consistently report magnetic saturation of our samples. We found that the dwell time seemingly has a stronger effect on particle sizes and magnetic saturation than the addition speed, within moderate addition rates, and further are we the first to report the effect of reaction temperature on semi-continuous synthesis. The iron oleate precursor obtained from salt exchange was employed without pretreatment or dilution thereby facilitating a streamlined synthesis process. An oxidative phase transfer was used to mitigate the key challenge of hydrophobicity of oleate-capped IONPs, enabling their potential use in biomedical applications. Our work advances the understanding of of synthesis-property relationships of IONPs by demonstrating the translation of established synthesis protocols into more efficient and scalable processes through which it provides insights for developing and optimizing future production protocols for various applications. Graphical abstract